2009
DOI: 10.1515/jpm.2009.032
|View full text |Cite
|
Sign up to set email alerts
|

Advanced maternal age as a sole indication for genetic amniocentesis; risk-benefit analysis based on a large database reflecting the current common practice

Abstract: Our analysis suggests that the benefit of genetic amniocentesis for the sole indication of AMA far outweighs the potential amniocentesis-related fetal loss rate, regardless of the actual rate one considers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…Some reports have suggested that maternal age Ն 35 years should not be used as the only indication for off ering invasive diagnostic testing (Berkowitz et al 2006;Hodges and Wallace 2005;Kuppermann and Norton 2005;ACOG 2007). However, Bornstein et al (2009) demonstrated that advanced maternal age is a reasonable indication for invasive prenatal diagnosis, although they acknowledge that this will result in a high rate of invasive procedures. When we evaluated our indications, no abnormality was detected by ultrasonography in 58.9% of the fetuses with chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports have suggested that maternal age Ն 35 years should not be used as the only indication for off ering invasive diagnostic testing (Berkowitz et al 2006;Hodges and Wallace 2005;Kuppermann and Norton 2005;ACOG 2007). However, Bornstein et al (2009) demonstrated that advanced maternal age is a reasonable indication for invasive prenatal diagnosis, although they acknowledge that this will result in a high rate of invasive procedures. When we evaluated our indications, no abnormality was detected by ultrasonography in 58.9% of the fetuses with chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the recently published guidelines, quite a few obstetricians still consider the age of 35 years as a cutoff for genetic testing [10]. According to recent studies conducted in Colorado of the US, birth rate of children with Down's syndrome increased when frequency of amniocentesis was reduced among women aged 35 years or older [11,12]. Consequently, maternal age is a factor that cannot be completely excluded from examination of fetal chromosomal abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that when a woman is 35 years or older (at the time of birth), the risk of miscarriage due to amniocentesis is lower than the probability of having a child with Down's syndrome *Manuscript (must not contain author information) Click here to view linked References 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 (Bornstein et al, 2009). Consequently, advanced maternal age (AMA) is the most common routine indication for genetic counseling during pregnancy (Drugan & Evans, 2006).…”
Section: Advanced Maternal Age and Prenatal Testingmentioning
confidence: 99%